Digital Intimacy and Marital Authority in Contemporary Muslim Families: Reconfiguring Consent and Obedience in the Age of Social Media - Arif Rahman (al-Rasῑkh: Jurnal Hukum Islam, 2026)
The disruption of information technology has deconstructed the boundaries of domestic privacy, giving rise to a virtual dimension that is prone to triggering trust crises when traditional expectations of obedience clash with the autonomy of cyberspace. In response to this condition, this research aims to reconfigure the concepts of consent, marital authority (qawwamah), and obedience (ta'ah) in contemporary Muslim families facing the challenges of digital intimacy. This study employs a qualitative method based on library research with a socio-legal approach, utilizing the analytical framework of Maqāṣid al-Sharī'ah. The findings indicate that a rigid understanding of authority in the digital age has the potential to spawn domestic authoritarianism. Obedience no longer means the unilateral, total surrender of gadget privacy; rather, it must be negotiated through the principle of mu’asyarah bil ma’ruf (living together in kindness) to prevent the occurrence of digital nushuz—a new form of emotional neglect caused by screen addiction and phubbing behavior. In conclusion, household integrity in the era of disruption can only be maintained through a transformation from physical surveillance control to the establishment of a participatory digital marital agreement. This research provides a theoretical contribution by expanding the meaning of nushuz into the digital realm and offers practical guidance for marriage counseling institutions in responding to technology-based domestic disputes.